Phytoformulation of Tagetes patula for Improving Permeability and Prevention of Hyperlipidaemia - Nawale, Sneha; Das, Sujit; N, Priyanka; M, Ganga Raju (Indian Journal of Pharmaceutical Education and Research, 2020)
The present study was aimed to formulate phytoformulation of Tagetes patula (MSTP) and its evaluation for antihyperlipidemic activity with triton X-100 and propyl thiouracil induced hyperlipidaemia models. Microsuspension of T. patula extract (50 and 100 mg; MSTP) was developed by precipitation technique. MSTP was assessed for its particle size, pH and drug entrapment efficacy. The results confirmed that microsuspension prepared with Tagetes patula extract (MSPT) showed average particle size 5.92 μm, pH 5.04 and 38 % drug entrapment. MSTP was screened for antihyperlipidemic activity with triton X-100 and propyl thiouracil induced hyperlipidaemia models. MSPT at doses 50 and 100 mg/kg; bd.wt,p.o proved a significant (p<0.01, p<0.05) antihyperlipidaemic potential by reducing levels of TG, TC, VLDL, LDL and shown raised HDL level when results were compared with normal and standard group in propyl thiouracil induced and triton X-100 induced hyperlipidaemia models. MSPT showed prominent antihyperlipidaemic activity as decreased particle size improves the dissolution and bioavailability of poorly soluble secondary metabolites. The results revealed significant antihyperlipidaemic activity for MSPT so can be used for managing hyperlipidaemia and other metabolic disorders.
Keywords: Tagetes patula; Micro suspension; Triton X-100; PTU; GC-MS